Development and application of GIS datasets for assessing and managing coastal impacts and future change on the central coast of Western Australia - Stevens, Alexandra; Collins, Lindsay (Springer, 2011)
The coastal zone between Guilderton and Kalbarri, north of Perth, Western Australia, is a highly dynamic area of high landscape and conservation values under increasing development pressures. Intensification of terrestrial and coastal impacts has highlighted the need to develop a georeferenced data base for land management. The Coastal Assessment and Restoration project aimed to document the natural resources and coastal developments to the region and to identify & assess threats to the coastal strip through the creation of GIS datasets. GIS datasets provide a key source of referenceinformation which can be accessed by a number of stakeholders for future coastal planning and management and provide a basis for developing a risk management assessment of the coastal zone and a strategy for coastal managers in our climate change future.